1990
DOI: 10.1007/bf00009260
|View full text |Cite
|
Sign up to set email alerts
|

Benefit and cost analysis and phosphorus efficiency of VA mycorrhizal fungi colonizations with sorghum (Sorghum bicolor) genotypes grown at varied phosphorus levels

Abstract: Sorghum [Sorghum bicolor (L.) Moench] was grown in a greenhouse in a low P (3.6mgkg -1) soil (Typic Argiudolls) inoculated with the vesicular-arbuscular mycorrhizal fungi (VMAF) Glomus fasciculatum and P added at 0, 12.5, 25.0, and 37.5 mgkg -1 soil to determine the effects of VAMF-root associations on plant growth, benefit and cost analysis, and P efficiency (dry matter produced/unit P absorbed). Root colonization with VAMF and shoot growth enhancements decreased with increased soil P applications. Mycorrhiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 18 publications
0
4
1
2
Order By: Relevance
“…Spore densities of different cropping systems seemed not to correlate with differences in soil P which varied considerably, from 4 to 45 mg P g soil -1 . This result disagrees with the wellknown fact that increasing amounts of phosphorus has a negative impact on mycorrhiza (Antunes and Cardoso 1991, Arias et al 1991, Bolan 1991, Fairchild and Miller 1990, Hung et al 1990, Raju et al 1990). Mårtensson and Carlgren (1993) Vestberg, M. et al Arbuscular mycorrhizal fungi in Bolivia found that the number of mycorrhizal spores decreased rapidly over time with increasing annual additions of a soluble phosphorus fertilizer.…”
Section: Discussioncontrasting
confidence: 74%
“…Spore densities of different cropping systems seemed not to correlate with differences in soil P which varied considerably, from 4 to 45 mg P g soil -1 . This result disagrees with the wellknown fact that increasing amounts of phosphorus has a negative impact on mycorrhiza (Antunes and Cardoso 1991, Arias et al 1991, Bolan 1991, Fairchild and Miller 1990, Hung et al 1990, Raju et al 1990). Mårtensson and Carlgren (1993) Vestberg, M. et al Arbuscular mycorrhizal fungi in Bolivia found that the number of mycorrhizal spores decreased rapidly over time with increasing annual additions of a soluble phosphorus fertilizer.…”
Section: Discussioncontrasting
confidence: 74%
“…Pearson & Jakobsen (1993) compared the efficiency of three AM fungi by measuring hyphal "%C use per unit $#P transported and below-ground "%C use per unit $#P transported. Both Tinker et al (1994) with ECM willow and Raju et al (1990) with AM sorghum calculated costs and benefits to the mycorrhizal plant in terms of C. Tinker et al (1994) determined that ECM willow converted 85 % of the extra C fixed into shoot biomass ( l C-use efficiency). Raju et al (1990) found that in a low-P soil, the percentage benefit of arbuscular mycorrhizas to the sorghum averaged 84 %, but the approach in this experiment was totally different and more related to the concepts suggested by Stribley, Tinker & Snellgrove (1980).…”
mentioning
confidence: 99%
“…A interação entre FMA e P em muitos vegetais importantes agronomicamente tem sido amplamente investigada (Raju et al 1990;Silva e Siqueira, 1991;Weber e Amorim, 1994), todos eles verificando maior absorção de P.…”
Section: Discussionunclassified